Percutaneous Mechanical Thrombectomy for Acute Limb Ischemia With Aorto-iliac Occlusion - Yang, Xinrui; Li, Xiangxiang; Yin, Minyi; Wang, Ruihua; Ye, Kaichuang; Lu, Xinwu; Li, Weimin; Cheng, Yong; Qin, Jinbao (Frontiers in Surgery, 2022)
Background: To evaluate the outcomes of percutaneous mechanical thrombectomy (PMT) in patients with acute lower limb ischemia (ALI) caused by aortic bifurcation embolism (ABE). Materials and Methods: Data of patients with ALI caused by ABE in our institutions from January 2015 and April 2020 were reviewed. The primary end point was limb salvage rate. The secondary end points included technical success rate, survival rate, complication. Results: A total of 85 patients with ALI was diagnosed with ABE. Thirty-eight patients were treated by PMT and enrolled in present study. Twenty-four were male (63.2%), and 14 were female (36.8%). The mean age was 66 years (range 28-83). All 38 patients were treated with PMT, with additional catheter directed thrombolysis (2/38,5.3%), balloon angioplasty (8/38,21.1%) and stent deployment (7/38,18.4%). The mean procedure time was 123 ± 31 minutes. Thirty-day limb salvage was 94.7% and limb salvage was 94.4%. The mean follow-up time was 14.0 months (8-22 months). There was no major amputation and target artery occlusion occurred during the follow-up period. Conclusions: PMT with Rotarex catheter could be new option for acute ABE, leading to safe and effective results.